Ecologies of care: qualitative insights from a psychosocial study on veterinarians’ experiences in Northeastern Italy - De Vincenzo, Ciro; Testoni, Ines (Frontiers in Veterinary Science, 2025)
Over the last decade, literature has raised concerns about the psychological well-being of veterinarians, highlighting exposure to economic, organizational, and clinical stressors. However, most research is quantitative and concentrated in Anglophone contexts (UK/US), leaving a significant gap in qualitative, EU-based data. While quantitative research highlights trends, qualitative methods offer in-depth insight crucial for developing tailored interventions. Addressing this gap, this study adopts a qualitative methodology informed by a psychosocial framework to explore the lived experiences of 20 companion animal veterinarians in Northeastern Italy. Semi-structured interviews were conducted and analyzed using Reflexive Thematic Analysis. Five themes were generated, revealing that veterinary science and veterinarians are undergoing a profound transformation within their evolving sociocultural role and mandate. Findings highlight tensions related to fragmented communities, socioemotional delegitimization, and the hidden weight of changing client dynamics. This ripple effect, marked by complex tensions affecting personal (expectations) and professional (caring function) domains, challenges the coherence and sustainability of their occupational identity and psychosocial well-being, requiring an ongoing labor of readaptation. The study concludes that contemporary psychosocial distress in veterinary work should not be understood solely through individual-level factors. Rather, distress reflects profound changes in the sociocultural landscape, including shifts in how human–animal relationships are framed and changing client expectations. This highlights a pressing need for veterinary science to engage in deeper dialog with the human and social sciences. An ecological perspective is essential for designing targeted systemic interventions, informing policy, and creating effective, context-sensitive training.